Knowledge, attitude, and practice toward non-nutritive sweeteners among the population with reduced sugar intake requirement - Chen, Qiao; Zhang, Yan; Li, Hui (Frontiers in Nutrition, 2024)
Introduction This study aimed to explore the knowledge, attitude, and practice (KAP) toward non-nutritive sweeteners among a population with reduced sugar intake requirements. Methods This cross-sectional study used self-developed questionnaires to collect demographic characteristics and KAP towards non-nutritive sweeteners among respondents with reduced sugar intake requirements, i.e., overweight or obese individuals and patients with pre-diabetes or diabetes. Results A total of 639 valid questionnaires were collected, and 51.64% of participants were male. The KAP scores were 7.63 ± 3.58 (range: 0–11), 34.28 ± 7.47 (range: 12–60), and 15.48 ± 3.97 (range: 7–35), respectively. Pearson’s correlation analysis showed that knowledge score was positively correlated with attitude (r = 0.229, p < 0.001) and practice score (r = 0.467, p < 0.001), while attitude was positively correlated with practice (r = 0.312, p < 0.001). The structural equation model showed that knowledge was directly and positively associated with attitude (path coefficient = 0.48, p < 0.001) and practice (path coefficient = 0.46, p < 0.001). In addition, the attitude was directly and positively associated with practice (path coefficient = 0.12, p < 0.001). Besides, diabetes was associated with lower knowledge (path coefficient = −0.81, p = 0.038) and practice (path coefficient = −0.42, p < 0.041). Discussion Population with the reduced sugar intake requirement showed poor knowledge, negative attitudes, and suboptimal practices toward non-nutritive sweeteners. To optimize the utilization of non-nutritive sweeteners in accordance with medical prescriptions, especially for individuals with diabetes, tailored educational interventions may be designed for participants with lower KAP.